Global institutional transformations and modern educational and scientific strategies for the paradigm of sustainable development of society - Віктор Зінченко (Cхід, 2022)
The article considers the processes of democratization of social institutions of education and science on the basis of the world-system global-stadial concept developed by the author and presented in his earlier works as an institutionalized process of functioning of deliberative socioeconomic development in the institutional model of globalization. The author considers “The 2030 Agenda for Sustainable Development” (UN) and the Global Action Program “Education for Sustainable Development” (UNESCO) as key documents shaping the tasks of further development of these social institutions. It highlights the key educational concepts for the transformation of the global world and shows how they correspond to the goals and objectives of these key international documents; substantiates specific directions for key areas of the educational goal of global sustainable development (for all levels of education), which should be included in the education and training system, formulates the tasks of further transformation of educational institutions; states that the principles of education defined in these global programs are most successfully implemented today within the framework of the “Education for Sustainable Development” model, which allows the formation of such key competencies as a sustainable lifestyle, knowledge of human rights and mechanisms for their observance, gender equality, promoting a culture of peace and non-violence and recognizing cultural diversity.